Clinicopathological and prognostic characteristics of idiopathic membranous nephropathy with dual antigen positivity - Yang, Lei; Wang, Guoqin; Ye, Nan; Xu, Xiaoyi; Cheng, Wenrong; Sun, Lijun; Dong, Hongrui; Kong, Lingqiang; Zhao, Xiaoyi; Geng, Yanqiu; Cheng, Hong (Frontiers in Immunology, 2024)
Background Idiopathic membranous nephropathy (IMN) is the most common pathological type in adults with nephrotic syndrome. Many target antigens have been discovered. However, dual antigen-positive IMN patients are very rare, with only a few such cases being briefly described in various studies. There is no specific study on the clinicopathological and prognostic characteristics of dual antigen-positive IMN patients, and the disease characteristics of such patients remain unclear. Methods Immunohistochemical staining of PLA2R, THSD7A, and NELL-1 was conducted on kidney tissue samples obtained from patients diagnosed with IMN. Simultaneously, the presence of corresponding serum antibodies was determined. Patients exhibiting positivity for dual antigens were included in the study, identified either through tissue staining or serum antibody detection. We retrospectively collected their clinical, pathological, and follow-up data and measured their serum antibody levels at multiple time points. Additionally, the same type of dual antigen-positive IMN cases reported in the literature were reviewed to extract clinical, pathological, and prognostic information. We compared the data for all of the above dual antigen-positive and PLA2R single-positive IMN cases at our center. Results We identified 6 IMN patients with dual antigen positivity at our center, approximately 0.7% of whole MN series; the previous literature reports IMN patients with dual antigen positivity, the proportion ranged from 0.2% to 2.8%. The IgG1 positivity rate in the renal tissue of the dual antigen-positive patients at our center was significantly lower than that of dual antigen-positive patients previously reported (16.7% vs. 100.0%, p=0.015), but there was no significant difference in clinical or prognostic aspects. Compared with PLA2R single-positive IMN, dual antigen-positive patients reported at our center and in the literature had a higher renal tissue IgG1 positivity rate (58.3% vs. 22.3%, p=0.016), and the time required to achieve remission was longer [13.5 (3.3,35.0) vs. 3.0 (1.0,8.0), p=0.052]. Overall, The changes in urine protein were consistent with the changes in serum PLA2R antibody levels in dual antigen-positive IMN patients. Conclusions For patients with primary membranous nephropathy who did not attain remission following prolonged treatment, multiple target antigen staining should still be actively performed, even with positivity for the PLA2R target antigen.